Effect of the Affective and Cognitive Benefits of Exercise in Instagram on Users' Physical Activity - Saeed Yousefi; Fatemeh Abdavi; Yaghoob Badriazarin; Maryam Moghadam Salimi (Shahid Bahonar University of Kerman, 2023)
The present research examined the effects of the affective and cognitive benefits of exercise in Instagram on users' physical activity through two consecutive studies. The results of the first study showed that the designed content provided sufficient cognitive and affective benefits. Similarly, the second study found that after adjusting the basic PA level, the affective and cognitive groups had more PA than the control group, and the cognitive group had more than the control group. Consecutively, 45.75% of subjects who were inactive were turned into active after one week of being taught of the benefits of exercise, with 71.43% in the affective group and 28.57% in the cognitive group. In terms of gender, 84.12% were women and 15.78% were men. As a result, visual exposure to sports participation might have led to an increase in positive feelings among users, especially women, which may have led to increased PA levels. The results of this study are useful for health professionals who are trying to communicate information about the benefits of exercise to their target audience based on a combination of evidence, gender, and PA level.